PERAN PEMUKA AGAMA MEMBANGUN ETIKA EKONOMI DALAM MASYARAKAT MULTIKULTURAL - Rany Claudia; Yudi Apriansyah; Rahma Madayanti; Ronaldo Juliyan Saputra (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
Indonesia's multicultural society consists of various religious, cultural and ethnic backgrounds, requiring economic ethics that can harmoniously accommodate diversity. Religious leaders have a strategic role in developing economic ethics based on moderate and inclusive religious moral and spiritual values. This study examines economic ethics from an interfaith perspective and the role of religious leaders in applying economic ethics to their congregations. The informants for this study were ten religious leaders from Islam, Catholicism, Protestantism, Hinduism, and Buddhism. This study used a qualitative method with a case study approach.The results of this study indicate that economic ethics from an interfaith perspective are conveyed through teaching, guidance, and example. Religious leaders play a role in instilling the principles of honesty, justice, responsibility, and solidarity in the economic activities of the community. In addition, religious leaders also play a role in facilitating interfaith dialogue to strengthen tolerance and economic cooperation across communities. This approach not only maintains social harmony but also encourages fair and sustainable economic empowerment, where religious leaders can become effective agents of social change in building economic ethics that support harmony and mutual prosperity.